M-Au/TiO2 (M = Ag, Pd, and Pt) nanophotocatalyst for overall solar water splitting: role of interfaces - Melvin, Ambrose A.; Illath, Kavya; Das, Tanmay; Raja, Thirumalaiswamy; Bhattacharyya, Somnath; Gopinath, Chinnakonda S. (Nanoscale, 2015)
M-Au/TiO2 (M = Ag, Pd, Pt) composites were prepared through a facile one-pot photodeposition synthesis and evaluated for solar water splitting (SWS) with and without a sacrificial agent. The M-Au combination exhibits a dominant role in augmenting the H2 generation activity by forming a bi-metallic system. Degussa P25 was used as a TiO2 substrate to photodeposit Au followed by Au + M (M = Ag/Pd/Pt). The SWS activity of the M-Au/TiO2 was determined through photocatalytic H-2 production in the presence of methanol as a sacrificial agent under one sun conditions with an AM1.5 filter. The highest H-2 yield was observed for Pt-0.5-Au-1/TiO2 and was around 1.3 +/- 0.07 mmol h(-1) g(-1), with an apparent quantum yield (AQY) of 6.4%. Pt-0.5-Au-1/TiO2 also demonstrated the same activity for 25 cycles of five hours each for 125 h. Critically, the same Pt-0.5-Au-1/TiO2 catalyst was active in overall SWS (OSWS) without any sacrificial agent, with an AQY = 0.8%. The amount of Au and/or Pt was varied to obtain the optimum composition and it was found that the Pt0.5-Au1/TiO2 composition exhibits the best activity. Detailed characterization by physico-chemical, spectral and microscopy measurements was carried out to obtain an in-depth understanding of the origin of the photocatalytic activity of Pt-0.5-Au-1/TiO2. These in-depth studies show that gold interacts predominantly with oxygen vacancies present on titania surfaces, and Pt preferentially interacts with gold for an effective electron-hole pair separation at Pt-Au interfaces and electron storage in metal particles. The Pt in Pt-0.5-Au-1/TiO2 is electronically and catalytically different from the Pt in Pt/TiO2 and it is predicted that the former suppresses the oxygen reduction reaction.

Is there any real effect of low dimensional morphologies towards light harvesting? a case study of Au-rGO-TiO2 nanocomposites - Melvin, Ambrose A.; Bharad, Pradnya A.; Illath, Kavya; Lawrence, Meenu P.; Gopinath, Chinnakonda S. (Chemistry Select, 2016)
Nanotube and nanosheet morphologies have been celebrated for their electron transport properties. Present work has been explored to exploit the same by combining 1D TiO2 nanotube (1D-TN) with 2D reduced graphene oxide (rGO) along with nano gold for visible light sensitization for photocatalytic H2 generation under one sun condition and visible light (λ≥ 400 nm). Vertical and horizontal electron transport in 1D-TN and rGO, respectively, is combined with the visible light absorption capability of Au nanoparticle. H2 yield (HY) varies between 100 and 655 µmol/g.h with an apparent quantum yield between 0.45 and 3.2 %, respectively, depending on Au/rGO/1D-TN preparation method and reaction conditions. It has been demonstrated that interfacial contact between rGO/1D-TN and Au is crucial for high photocatalytic HY. Preparation method influences charge utilization, and hence HY, to a large extent. Nonetheless, the maximum HY reported in the present work is just comparable to HY reported in literature with the most commonly found spherical morphology, and this leads to a question of, is there any real influence of 1D and/or 2D materials, particularly, towards light harvesting applications?

Multi-mode hydrogen storage in nanocontainers - Shervani, Suboohi; Mukherjee, Puspal; Gupta, Anshul; Mishra, Gargi; Illath, Kavya; Ajithkumar, Thallaseril G.; Sivakumar, Sri; Sen, Pratik; Balani, Kantesh; Subramaniam, Anandh (International Journal of Hydrogen Energy, 2017)
Hydrogen can be stored in containers or in materials (in molecular or atomic forms). The atomic form can further exist as multiple phases. Molecular hydrogen can be adsorbed on the surface or can be present inside the material. By invoking multiple modes of hydrogen storage, we establish a paradigm shift in the philosophy of hydrogen storage. Using a novel strategy of storage of molecular hydrogen in metal (Pd) nanocontainers, we observe that 18% hydrogen is in molecular form. Interestingly, this is achieved at 25 °C and 1 atm pressure; which is in contrast to storage in MOFs and carbonaceous materials like nanotubes. Enhancement in storage capacity as compared to Pd nanocrystals of the same mass is observed (36% increase at 1 atm & 25 °C), along with fast kinetics (0.5 wt% hydrogen absorption in 5 s). A new mechanism for hydrogen storage involving the dual catalytic role of Pd is established.

Distribution of water in the pores of periodic mesoporous organosilicates - a proton solid state MAS NMR study - Veena, V. S.; Illath, Kavya; Lazar, Anish; Vinod, C. P.; Ajithkumar, T. G.; Jayanthi, S. (Physical Chemistry Chemical Physics, 2018)
Solid state proton (H-1) magic angle spinning (MAS) NMR has been employed to study the distribution of confined water in ethane substituted periodic mesoporous organosilicate (PMOE) materials. Proton spectra acquired at different hydration levels are analysed and interpreted in terms of water clusters of various sizes and distributions of water layers on the pore surface. For comparison, we also performed similar experiments on SBA-15. The formation of larger clusters at lower hydration suggests that the pores of PMOE are getting filled with water at lower hydration levels than those in SBA-15. For PMOE, the simultaneous presence of two major resonances in the ranges 3.6-4.1 ppm and 4.4-5.2 ppm and their behaviour upon hydration imply a water layer distribution that is the sum of two contributions, corresponding to fully filled and partially filled pores or pore segments. Furthermore, the behaviour mentioned above suggests that both radial and axial filling mechanisms play a significant role in the hydration process. For SBA-15, as a function of hydration, we observed a smooth variation in the proton chemical shift of the main dynamic resonance. In accordance with previous studies, this is attributed to the gradual increase in the average thickness of water layers with an increase in hydration, and to a pore filling mechanism that is predominantly radial.

Preparation of colourless phosphate glass by stabilising higher Fe[II] in microwave heating - Mandal, Ashis K.; Mandal, B.; Illath, Kavya; Ajithkumar, T. G.; Halder, A.; Sinha, P. K.; Sen, Ranjan (Scientific Reports, 2018)
Iron impurity in raw material remains a major challenge in producing colourless glass. In this investigation, we report microwave (MW) heating capable of altering Fe-redox ratio (Fe2+/Sigma Fe) enabling preparation of colourless phosphate glass. The effect of Sn concentration in retention of Fe[II] in glass melted in MW was compared with conventional glasses. Colourimetric study developing Fe2+-ferrozine colour complex reveals Fe-redox ratio >= 0.49 required to obtain colourless phosphate glass. In microwave heating, addition of 1 wt.% Sn metal powder can impart the desired effect whereas addition of 1.9 wt.% Sn metal powder is required in conventional heating. The correlation equation of Fe-redox ratio with concentration of Sn metal is found to be different in microwave and conventional heating. Thus, exploiting this different redox changes in MW heating optical properties can be tailored. Preservation of higher Fe[II] in MW melted glass is also confirmed by XPS and TGA. P-31 MAS NMR spectra suggest that transition from cross linked ultra phosphate to linear polymer metaphosphate network in incorporation of Sn is found different in glass prepared adopting microwave irradiation. (27)A1 MAS NMR spectra suggest higher relative content of Al6+ in glass obtained from MW heating. Energy consumption analysis revels 3.4 kWh in MW heating while 14 kWh in conventional glass melting using resistance heating. Further, glass melting in MW can be completed within 2 h unlike similar to 5 h needed in conventional. MW heating plays a significant role in improving properties to make colourless phosphate glass in addition to significant energy and time saving.

Structural elucidation of NASICON (Na3Al2P3O12) based glass electrolyte materials: effective influence of boron and gallium - Allu, Amarnath R. (RSC Advances, 2018)
Understanding the conductivity variations induced by compositional changes in sodium super ionic conducting (NASICON) glass materials is highly relevant for applications such as solid electrolytes for sodium (Na) ion batteries. In the research reported in this paper, NASICON-based NCAP glass (Na2.8Ca0.1Al2P3O12) was selected as the parent glass. The present study demonstrates the changes in the Na+ ion conductivity of NCAP bulk glass with the substitution of boron (NCABP: Na2.8Ca0.1Al2B0.5P2.7O12) and gallium (NCAGP: Na2.8Ca0.1Al2Ga0.5P2.7O12) for phosphorus and the resulting structural variations found in the glass network. For a detailed structural analysis of NCAP, NCABP and NCAGP glasses, micro-Raman and magic angle spinning-nuclear magnetic resonance (MAS-NMR) spectroscopic techniques (for 31P, 27Al, 23Na, 11B and 71Ga nuclei) were used. The Raman spectrum revealed that the NCAP glass structure is more analogous to the AlPO4 mesoporous glass structure. The 31P MAS-NMR spectrum illustrated that the NCAP glass structure consists of a high concentration of Q0 (3Al) units, followed by Q0 (2Al) units. The 27Al MAS-NMR spectrum indicates that alumina exists at five different sites, which include AlO4 units surrounded by AlO6 units, Al(OP)4, Al(OP)5, Al(OAl)6 and Al(OP)6, in the NCAP glass structure. The 31P, 27Al and 11B MAS-NMR spectra of the NCABP glass revealed the absence of B–O–Al linkages and the presence of B3–O–B4–O–P4 linkages which further leads to the formation of borate and borophosphate domains. The 71Ga MAS-NMR spectrum suggests that gallium cations in the NCAGP glass compete with the alumina cations and occupy four (GaO4), five (GaO5) and six (GaO6) coordinated sites. The Raman spectrum of NCAGP glass indicates that sodium cations have also been substituted by gallium cations in the NCAP glass structure. From impedance analysis, the dc conductivity of the NCAP glass (∼3.13 × 10−8 S cm−1) is slightly decreased with the substitution of gallium (∼2.27 × 10−8 S cm−1) but considerably decreased with the substitution of boron (∼1.46 × 10−8 S cm−1). The variation in the conductivity values are described based on the structural changes of NCAP glass with the substitution of gallium and boron.

Elucidating the effect of CaF 2 on structure, biocompatibility and antibacterial properties of S53P4 glass - Prasad, Sakthi; Ganisetti, Sudheer; Jana, Anuradha; Kant, Shashi; Sinha, P. K.; Tripathy, Sucheta; Illath, Kavya; Ajithkumar, T. G.; Annapurna, K.; Allu, Amarnath R.; Biswas, Kaushik (Journal of Alloys and Compounds, 2020)
<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">The present work focuses on the synthesis and structural elucidation of fluoride containing bioactive glasses in the system (in mol%) given by (53.86) SiO<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> – (22.65) Na<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O – (21.77-x) CaO – (1.72) P<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">5<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> – x CaF<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">, where, x = 0, 5.44, 10.885 and 16.33. The role of the incorporated fluoride and its distribution within the glass were interpreted and analyzed using Molecular dynamics (MD) simulations and the results were compared with the modified random network (MRN) model. The interpretations from the model have been verified using the MAS-NMR spectroscopy technique. According to this model, fluoride containing bioactive glasses have been proposed to consist of silicate rich network regions and modifier cation – fluoride rich inter-network regions. The interface region was found to consist of non-bridging oxygen species (NBO) and phosphate cations which are either isolated orthophosphates (<em style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Q<span style="font-size: 13.5px; line-height: 0; position: relative; top: -0.5em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">0<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">P<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">) or bridged with silicates in the form of pyrophosphate (<em style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Q<span style="font-size: 13.5px; line-height: 0; position: relative; top: -0.5em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">1<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">P<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">) units forming Si–O–P bonds. The gradual substitution of CaF<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> for CaO in the base glass resulted in an increase in the silicate network connectivity with a reduction in the NBOs and lead to an increase in the association of modifier cations with fluoride ions. However, fluoride ions were found to show a marginal preference to associate with Na<span style="font-size: 13.5px; line-height: 0; position: relative; top: -0.5em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">+<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> cations leading to a decrease in the association of Na<span style="font-size: 13.5px; line-height: 0; position: relative; top: -0.5em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">+<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> ions with orthophosphate and silicate units. These overall structural findings were correlated with the <em style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">in vitro<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> ion dissolution behaviour of the bioactive glasses as well as with the thermal properties. The glasses were tested for their <em style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">in vitro<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> cell viability towards mouse osteoblast type (MC3T3) cells in which fluoride containing bioactive glasses did not show any toxicity and exhibited better cell proliferation. The antibacterial efficacy of the fluoride containing glasses was tested at various concentrations (5, 10 and 20 mg/ml) in <em style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">E.coli<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> bacterial inoculum in which bactericidal action was evidenced.
Keywords: Fluoride bioactive glasses; In vitro apatite formation and bactericidal action; MAS-NMR spectroscopy; MD simulations

Elucidating the effect of CaF2 on structure, biocompatibility and antibacterial properties of S53P4 glass (vol 831, 154704, 2020) - Prasad, Sakthi; Ganisetti, Sudheer; Jana, Anuradha; Kant, Shashi; Sinha, P. K.; Tripathy, Sucheta; Illath, Kavya; Ajithkumar, T. G.; Annapurna, K.; Allu, Amarnath R.; Biswas, Kaushik (Journal of Alloys and Compounds, 2021)

Ionic conductivity of Na3Al2P3O12 glass electrolytes role of charge compensators - Keshri, Shweta R.; Ganisetti, Sudheer; Kumar, Rajesh; Gaddam, Anuraag; Illath, Kavya; Ajithkumar, Thalasseril G.; Balaji, Sathravada; Annapurna, K.; Nasani, Narendar; Krishnan, N. M. Anoop; Allu, Amarnath R. (Inorganic Chemistry, 2021)
In glasses, a sodium ion (Na+) is a significant mobile cation that takes up a dual role, that is, as a charge compensator and also as a network modifier. As a network modifier, Na+ cations modify the structural distributions and create nonbridging oxygens. As a charge compensator, Na+ cations provide imbalanced charge for oxygen that is linked between two network-forming tetrahedra. However, the factors controlling the mobility of Na+ ions in glasses, which in turn affects the ionic conductivity, remain unclear. In the current work, using high-fidelity experiments and atomistic simulations, we demonstrate that the ionic conductivity of the Na3Al2P3O12 (Si0) glass material is dependent not only on the concentration of Na+ charge carriers but also on the number of charge-compensated oxygens within its first coordination sphere. To investigate, we chose a series of glasses formulated by the substitution of Si for P in Si0 glass based on the hypothesis that Si substitution in the presence of Na+ cations increases the number of SiOAl bonds, which enhances the role of Na as a charge compensator. The structural and conductivity properties of bulk glass materials are evaluated by molecular dynamics (MD) simulations, magic angle spinning-nuclear magnetic resonance, Raman spectroscopy, and impedance spectroscopy. We observe that the increasing number of charge-imbalanced bridging oxygens (BOs) with the substitution of Si for P in Si0 glass enhances the ionic conductivity by an order of magnitudefrom 3.7 x 10(-8) S.cm(-1) to 3.3 x 10(7) S.cm(-1) at 100 degrees C. By rigorously quantifying the channel regions in the glass structure, using MD simulations, we demonstrate that the enhanced ionic conductivity can be attributed to the increased connectivity of Na-rich channels because of the increased charge-compensated BOs around the Na atoms. Overall, this study provides new insights for designing next-generation glass-based electrolytes with superior ionic conductivity for Na-ion batteries

Synthesis and characterization of LAGP-glass-ceramics-based composite solid polymer electrolyte for solid-state Li-ion battery application - Das, Anurup; Goswami, Madhumita; Illath, Kavya; Ajithkumar, T. G.; Arya, A.; Krishnan, M. (Journal of Non-Crystalline Solids, 2021)
Solid State Electrolytes (SSEs) are the future alternatives of the present conventional liquid electrolytes in terms of safety, high temperature stability and also good electrochemical performance. Glass (G), based on Lithium Aluminium Germanium Phosphate (LAGP) was prepared and converted into glass-ceramics (GC) by optimized heating schedule. The crystalline LAGP has Na Super Ionic CONductor (NASICON) type unit cell where the lithium ions hop between two different positions providing long range ionic motion. To improve the inter electrode surface resistance and cell performance, Composite Solid Electrolyte (CSE) was prepared with poly (vinylidene fluoride-co-hexaflurophoaphate) (P(VDF-HFP)), 20wt% LAGP, Lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and 1-Ethyl-3-methylimidazolium bis-(trifluoromethylsulfonyl)-imide (EMITFSI). X-ray diffraction patterns confirm the formation of the NASICON phase in LAGP GC and the amorphous nature of the CSE. NMR studies confirm formation of the Ge/AlO6 octahedra and PO4 tetrahedra inside the crystal. 7Li NMR also confirmed two different Lithium sites in LAGP crystal. The ionic conductivity values of CSE and LAGP GC are (4.49 +/- 0.31) x 10(-3)Scm(-1) and (2.70 +/- 0.04) x 10(-4)Scm(-1), respectively. The thermal stability of the prepared CSE is tested upto 315 degrees C without any degradation. Two cells (Cell-I & Cell-II) were fabricated using the LAGP GC and CSE respectively. Cell-II shows the specific discharge capacity of 151mAhg1 at 50th cycle which is higher as compared to Cell-I (129mAhg(-1)) when tested at the C-rate of 0.05 degrees C.
Keywords: Lithium germanium phosphate; NASICON; Solid state electrolyte; Solid state NMR

Investigation of Al2O3 induced variations in the structural parameters in strontium borosilicate glasses using solid state NMR - Illath, Kavya; Ojha, Prasanta K.; Rath, Sangram K.; Ajithkumar, T. G. (Physical Chemistry Chemical Physics, 2023)
The physical properties of oxide glasses are crucially dependent on the atomistic structural speciation. In this study, we investigate the variation in the local ordering in the glass network of strontium borosilicate glasses (34.82 SrO, 51.84 B2O3, 13.34 SiO2 in mol%) with a progressive substitution of B2O3 by Al2O3 and estimate the structural parameters: the oxygen packing fraction, and the average network coordination number. The coordination of the network forming cations at various glass compositions is determined using B-11, Al-27, and Si-29 solid-state nuclear magnetic resonance (SSNMR). The SSNMR reveals that at the higher substitution of B2O3 by Al2O3 in the glass composition, the coordination network of Al3+ exists predominantly in the 4 coordinated state, the network forming B3+ cations transform from a tetrahedral BO4 to a trigonal BO3 structure, and the Q(4) form of silicates is dominant. The average coordination number and the oxygen packing fraction were calculated using the parameters obtained from the SSNMR results, and it is observed that the average coordination number decreases, and the oxygen packing fraction increases on incorporating Al. It is interesting to note that some of the thermophysical properties of these compositions closely follow the pattern shown by the average coordination number and the oxygen packing fraction.

Insights into the Chemical Durability and Structure of ZnO-Incorporated Sodium Borosilicate Glasses from Solid-State NMR - Illath, Kavya; Ananthanarayanan, Arvind; Banerjee, D.; Mishra, R. K.; Kumar, Ravi; Bhattacharya, D.; Kumar, Sanjay; Manohar, S.; Ajithkumar, T. G. (Journal of Physical Chemistry B, 2025)
ZnO-incorporated NBS glasses have been studied for their application as a matrix for nuclear waste immobilization. However, structural factors affecting chemical durability have not been established. In this study, the structural changes in NBSZn glasses across various Na2O/(B2O3 + ZnO) ratios are explored using multinuclear MAS, MQMAS NMR, and EXAFS techniques. The Na MAS and MQMAS studies reveal remarkable changes in the Na environment after ZnO incorporation, which leads to an increase in chemical durability. Based on the results from NMR and EXAFS, we rationalized the structure of this glass in terms of the modified random network (MRN) model. The glass network comprises a highly polymerized region and alkali percolation channels bordered by nonbridging oxygens from the depolymerized regions. The constriction of these percolation channels increases the chemical durability of the glass. Our findings will help in the advancement of Zn-containing NBS glasses as a promising matrix for nuclear waste immobilization.